2000
DOI: 10.1097/00005392-200009010-00029
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Patient Reported Urinary Continence After Radical Prostatectomy

Abstract: The nerve sparing technique of radical prostatectomy was associated with improved recovery of urinary continence in an age dependent manner, whereas bladder neck preservation was not beneficial. Patient age and the sensitivity of the incontinence definitions, as reflected by the associated variable rates of preoperative baseline incontinence, are significant contexts for interpreting urinary function data after radical prostatectomy. These factors may partially explain the variation in continence rates in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(71 citation statements)
references
References 20 publications
7
60
2
1
Order By: Relevance
“…We were also able to group studies according to identical time points for follow-up patient assessments. The use of patient-reported pad use and subjective reports of UI for continence definition and assessment following RP has, however, been questioned by some authors [3,32] and supported by others [3,7,3133]. The approach used to define and assess UI after RP surgery in this systematic review, however, remains clinically accessible and widely used.…”
Section: Discussionmentioning
confidence: 99%
“…We were also able to group studies according to identical time points for follow-up patient assessments. The use of patient-reported pad use and subjective reports of UI for continence definition and assessment following RP has, however, been questioned by some authors [3,32] and supported by others [3,7,3133]. The approach used to define and assess UI after RP surgery in this systematic review, however, remains clinically accessible and widely used.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the paucity of long-term studies and the lack of a universally agreed upon definition of continence. Definitions used in the literature include daily use of no pads [6,10,12], daily use of up to one pad [6,13,26,27], total control or occasional dribbling [9,13,14,28], no problem dripping or leaking urine [26], and leaking once daily [26]. To better identify how men self-define continence status, Lepor et al correlated responses to the UCLA-PCI-UFI and patients’ self-assessments of whether they considered themselves continent or incontinent [29].…”
Section: Discussionmentioning
confidence: 99%
“…Bladder neck preservation (BNP), first introduced in 1992 by Klein [11], has been proposed as a method to accelerate continence recovery, as BNP during RP promotes early return of urinary continence and erectile function [1216]. However, some clinical trials have suggested little difference in the return of continence with BNP [1719], and risk of a positive surgical margin (PSM) may be increased [18, 2022]. …”
Section: Introductionmentioning
confidence: 99%